ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Nurul Hidayah, 12.05.52.0078; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2016)
The objective of this study is to examine and analyze the influence of profitability, liquidity, company size, board of commissioner, and institutional ownership to corporate social responsibility disclosure among manufacturing sector which listed on Indonesia Stock Exchange. This research was conducted in Indonesia Stock Exchange with purposive sampling method whit the sample was taken from the pereiod of 2012-2015. The sample collected includes 136 companies which satisfied some kriteria. Technique test of data is by using multiple linear reggression. These result indicste that board of commissioner is significant positively influence the corporate social responsibility disclosure. Thus, the result of those test provide support for the hypothesized. Profitability, liquidity, company size, and institutional ownership isn’t influence the corporate social responsibility disclosure at all.Keywords: Influence of Profitability, Liquidity, Company Size, Board of Commissioner, Institutional Ownership, Corporate Social Responsibility Disclosure